Communicating Climate Change: Lessons Learned from a Researcher-Museum Collaboration - Christopher T. Parker (American Society for Microbiology, 2018)
The need for science education and outreach is great. However, despite the ever-growing body of available scientific information, facts are often misrepresented to or misunderstood by the general public. This can result in uninformed decisions that negatively impact society at both individual and community levels. One solution to this problem is to make scientific information more available to the public through outreach programs. Most outreach programs, however, focus on health initiatives, STEM programs, or young audiences exclusively. This article describes a collaboration between the Research and Learning Center at the Fort Worth Museum of Science and History and an interdisciplinary team of researchers from the Dallas–Fort Worth (DFW) metroplex area. The collaboration was a pilot effort of a science communication fellowship and was designed to train researchers to effectively convey current science information to the public with a focus on lifelong learning. We focus on the broader idea of a university-museum collaboration that bridges the science communication gap as we outline the process of forming this collaboration, lessons we learned from the process, and directions that can support future collaborations.